(untitled) (Sociologisk Forskning, 1996)
Modern fathers - between tradition and relation Research on families simultaneously shows change and instability and duration and stability. Research on men as fathers bears the same contradiction, showing a man, who has got both traditional and more family and relation oriented characteristics. By asking men and women to tell about their life plans, their experiences of family life, gender and equality, we have tried to get hold of changes between ideal and gender identity, within the family context. The results show that the family with the focus on the children dominates the life plan of men and of women. We also find great similarities between the sexes in what they tell as about their family project. Differences appear, however, in what men and women tell us about what they do in their everyday family praxis. In the conflict between traditional roles, equality and every day praxis, men and women create routines which are effective, but also producing ambivalence in the conception of one self as parent, sex partner and equal partner of a married couple.